Factors related to use of prostate cancer screening: the Alberta Tomorrow Project - Richardson, Harriet (Open Medicine Publications, Inc., 2007)
BACKGROUND: Very few data are available on the determinants of PSA testing in Canada, and it is a matter of debate whether prostate-specific antigen (PSA) screening in asymptomatic men age 50 and older with no risk factors for prostate cancer is useful. If PSA screening is introduced into the periodic health examination, it will be important to know what factors influence its use. OBJECTIVES: The purpose of this study is to determine the factors associated with PSA testing among asymptomatic men age 50 and older participating in the Tomorrow Project in Alberta. METHODS: The Tomorrow Project is a population-based cohort study with over 11,000 participants accrued in Alberta since February 2003. Information was collected on medical history, sociodemographic factors, health status and lifestyle characteristics. This analysis includes 2136 men 50 years of age and older. The independent association between various factors and recent PSA screening is estimated using logistic regression. RESULTS: Approximately 50% of of the study group had received one or more PSA tests in their lifetime. Of these, 58% were asymptomatic for prostate disease at the time of their most recent PSA test. Variables independently associated with recent PSA screening for prostate cancer in this population include older age (≥ 65 versus < 55 years: adjusted odds ratio [OR] 2.60; 95% confidence interval [CI] 1.77–3.83), higher income (≥ $80,000 versus < $20,000, OR 1.97; 95% CI 1.09–3.55), region of health care delivery, perception of health status (good versus excellent health status; OR 0.65, CI 0.43–0.96], increased number of chronic health conditions (OR 1.73, 95% CI 1.10–2.71), and history of colorectal cancer screening with fecal occult blood test (OR 2.21; 95% CI 1.73–2.83). CONCLUSIONS: An increasing proportion of men in Alberta are receiving a PSA test. A number of significant predictors of having a PSA test were identified, suggesting that factors other than having a clinical indication for prostate disease can influence decisions about PSA screening.